Restructuring Marketing Systems for Small holders: Cases in Zimbabwe - Blackie, Malcom J. (International Food Policy Research Institute, 1987)
The failure of Zimbabwe and other African countries to develop agricultural delivery systems that serve the specific needs of the numerically dominant smallholder producers underlies the decline in agriculture in the region. A major cause of this failure is the complexity of the environment in which these systems must operate. Production units are dispersed with low levels of money income, savings, and capital. Purchases of inputs and sales of outputs are small and vary widely by seasons. The biological and seasonal nature of agricultural production, poor communications, and limited infrastructure add further complexity.